Distinct modes of interaction within eIF4F-like complexes and susceptibility to the RocA inhibitor for the Trypanosoma brucei EIF4AI translation initiation factor - Danielle M. N. Moura; Amanda L. Soares; Adalúcia da Silva; João L. A. B. Ribeiro; Jack D. Sunter; Ludmila A. Assis; Mark Carrington; Osvaldo P. de Melo Neto (PLoS ONE, 2025)
Trypanosomatids are parasitic protozoa responsible for major human diseases which are characterized by unique gene expression mechanisms. mRNA translation in these parasites is associated with multiple eIF4F-like complexes, required for mRNA recruitment and ribosome binding. The eukaryotic eIF4F is generally known to require the action of eIF4A, an ATP-dependent RNA helicase, in order to function properly, but not all trypanosomatid eIF4F complexes might require EIF4AI, their single eIF4A homologue. In mammals, eIF4A is known to be targeted by specific inhibitors and can thus be considered a potential target for a selective inhibition of translation in these parasites. Here, aiming to better define the EIF4AI functionality, we started by investigating its interactome in Trypanosoma brucei, confirming a strong interaction with only one of five eIF4F-like complexes found in trypanosomatids, based on the EIF4E4/EIF4G3 subunits. Nevertheless, when the interactome of a mutant EIF4AI (DEAD/DQAD), known to be impacted on its ATPase activity, was investigated, the only eIF4F-like complex found was based on the EIF4E3/EIF4G4 pair, with many translation-related and other proteins also found with the mutant protein. When both wild-type and mutant proteins were also investigated through a fluorescent-based tethering assay, a stimulatory effect on mRNA expression was confirmed for EIF4AI, but not for the mutant protein. Sensitivity to the Rocaglamide A (RocA) inhibitor, which targets the mammalian eIF4A, was also investigated, with the inhibitor blocking the stimulation seen on the tethering assay. Parasite susceptibility to RocA was further assessed in T. brucei and Leishmania infantum, with both, and specially T. brucei, being much less susceptible to the drug than mammalian cells. This phenotype correlates with changes in EIF4AI within the RocA binding pocket where, in comparison with the mammalian eIF4A, a phenylalanine to valine substitution in the T. brucei EIF4AI likely impairs RocA binding. Our results help better define the EIF4AI mode of action in T. brucei and provide relevant data which might support future searches for specific EIF4AI inhibitors.